Odpowiedź :
a)
2x²+1≤(x+5)²+(x-2)²
2x²+1≤x²+10x+25+x²-4x+4
2x²+1≤x²+x²+10x-4x+25+4
2x²+1≤2x+6x+29
1≤6x+29
-6x≤29-1
-6x≤28 |:(-6)
x≥-4 2/3
x∈<-4 2/3, +∞)
b)
5x²+3=8x
5x²-8x+3=0
Δ=(-8)²-4·5·3
Δ=64-60
Δ=4
√Δ=√4=2
x₁=(8+2)/(2·5)=10/10=1
x₂=(8-2)/(2·5)=6/10=3/5
c)
(x-4)(2-x)<0
x-4<0 ∨ 2-x<0
x<4 ∨ 2>x
x∈(-∞,2)∪(4,+∞)
Odpowiedź:
a)2x²+1≤(x+5)²+(x-2)²
2x²+1≤x²+10x+25+x²-4x+4
2x²+1≤2x²+6x+29
1≤6x+29
-6x≤29-1
-6x≤28/:(-6)
x≥-14/3
x≥-4 [tex]\frac{2}{3}[/tex]
x≥-4,6
b(
5x²+3=8x
5x²-8x+3=0
a=5.b=-8,c=3
Δ=b²-4ac=64-60=4
√Δ=√4=2
x₂=-b+√Δ/2a=1
x₁=1
x₂=-b-√Δ/2a=0,6
x₂=0,6
c)(x-4)(2-x)<0
2x-x²-8+4x<0
-x²+6x-8<0
a=-1,b=6,c=-8
Δ=b²-4ac
Δ=36-32=4
√Δ=2
x₁=-b+√Δ/2a
x₁=-6+2/-2
x₁=2
x₂=-b-√Δ/2a
x₂=-6-2/-2
x₂=4
x∈(-∞2)∪(4,+∞)
Szczegółowe wyjaśnienie: